PROTOTYPE DETEKSI LEVEL KANTUK BERDASARKAN EYE ASPECT RATIO MENGGUNAKAN METODE FACIAL LANDMARK BERBASIS ORANGE Pi - Am, Andri Nofiar (AMIK Mitra Gama, 2024)
The Prototype for Detecting Drowsiness Levels based on Eye Aspect Ratio using the Orange Pi-based Facial Landmark Method is a tool that can detect users in three levels of drowsiness, namely normal, drowsiness, or asleep. This tool uses EAR threshold parameters and utilizes the facial landmark method to detect points on the eye. The test results showed that the prototype device was able to function well after undergoing tests on distance, camera angle, eye size, use of glasses and light intensity. At testing distances of 25 cm, 35 cm, 50 cm, 70 cm, 85 cm, 100 cm, 130 cm and 155 cm, the tool can detect the user's eyes according to conditions. However, in tests based on angles it was found that the tool could detect the user's eyes at angles of 90o, 80o and 70o, except at the 60o angle due to the limited viewing angle of the camera so the tool could not detect the condition of the user's eyes at that angle.